2020
DOI: 10.9734/jocamr/2020/v9i430146
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Ascorbic Acid and Allium sativum (Garlic) Ethanol Extract on Renal Parenchyma of Gentamicin-induced Nephropathic Rats

Abstract: To assess ameliorative effects of Ascorbic acid (AA) and Allium sativum ethanol extract (ASEE) on renal parenchyma of gentamicin-induced nephropathic rats. Thirty Wistar rats (weighing between 180-205 g) were randomly divided into five groups (A-E).  These include Group A administered with 0.9% Normal Saline (0.5 ml/kg body weight (b.w.)), Group B administered with gentamicin (GM, 200 mg/kg b.w.) intraperitoneally (i.p.), Group C administered with GM (200 mg/kg b.w.) i.p. and AA (200 mg/kg b.w.) orally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to the findings of this study, exposure to methanol extract of C. bicolor causes significant (p<0.05) comparative reduction in the body and hepatic tissue weight of experimental animals (Figure 1). Previous studies have reported that such weight changes can be associated with the deleterious effect of exposure of xenobiotics including certain phytochemical constituents [39,40].…”
Section: Hepatic Histopathological Resultsmentioning
confidence: 99%
“…According to the findings of this study, exposure to methanol extract of C. bicolor causes significant (p<0.05) comparative reduction in the body and hepatic tissue weight of experimental animals (Figure 1). Previous studies have reported that such weight changes can be associated with the deleterious effect of exposure of xenobiotics including certain phytochemical constituents [39,40].…”
Section: Hepatic Histopathological Resultsmentioning
confidence: 99%
“…These include gastric mucosal surface erosion and degeneration of intestinal epithelium and villi. Generally, studies have suggested that widespread toxic effect of toxic substances in the body may cause distinct organ weight loss which can culminate into cumulative body weight reduction [22,23]. Accordingly, the significant reduction in body weight among treatment groups (I-III) compared to the control group can be associated with adverse effects of the plant extract on experimental animals in this study.…”
Section: Effect Of Methanolic Leaf Extract Of C Bicolor On Histomorpmentioning
confidence: 67%
“…Ascorbic acid is a potent natural antioxidant that can minimize oxidative stress, scavenge free radicals, and restabilize antioxidative systems. In many previous studies, AA has been used to reduce gentamicin-associated oxidative stress [ 10 , 45 , 50 , 51 ]…”
Section: Discussionmentioning
confidence: 99%